Integration of AHP and TOPSIS in a Web-Based Decision Support System for Wedding Package Selection - Cindya Putri Hidayat Siregar; M. Fakhriza (Journal of Information Systems and Technology Research, 2025)
The rapid growth of information technology has significantly influenced service industries, including the wedding sector, where customers often face difficulties in selecting the most suitable package from many available alternatives. To address this challenge, this study designed a web-based Decision Support System (DSS) by integrating the Analytic Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The research was conducted at Putri Darma Make Up, Medan, Indonesia, using customer preference records collected between January and May 2025. AHP was applied to determine the weights of decision criteria, yielding Facilities (0.521) and Decoration (0.297) as the most important, while Makeup Quality (0.058) received the lowest weight. TOPSIS was then used to evaluate and rank the alternatives. Results showed that the wedding package priced at 25 million IDR achieved the highest preference score (Ci = 0.937), followed by the 22 million IDR package (Ci = 0.662), while the 12 million IDR package had the lowest score (Ci = 0.301). These findings demonstrate consistency between AHP weight priorities and TOPSIS rankings, confirming the reliability of the system. The study contributes theoretically by applying multi-criteria decision-making to the wedding service industry and practically by providing a transparent tool that reduces subjectivity, accelerates decision-making, and improves customer satisfaction.